- The ability of the ministry of National Guard to achieve job satisfaction for employees - A field study - Al-Rashidi, Abdulmohsen Ghazi (Journal of Economic, Administrative and Legal Sciences, 2018)
Objectives of the study: The aim of this study was to identify the job-related factors that contribute to the job satisfaction which include wages, coworkers, leadership/supervision, promotion, rank, experience, training and social level. The study also aimed to know the personal factors that contribute to the job satisfaction that include age, the level of education and marital status. The study also sought to propose the necessary recommendations to improve the level of job satisfaction among workers in the Presidency of the National Guard. Methodology: To achieve these objectives the researcher used social survey method. The survey has been used as a tool to collect data of the study and was designed by taking advantage of previous studies related the subject. The design was applied to targeted population, consisting of all civil servants who work under the Chairmanship of the National Guard in Riyadh, and who hold civilian positions ranked from grade one to grade fourteen. The study excluded the military and non-official employees. Sample of the study: From eighteen departments and using a simple random sampling, the researcher selected five departments. Initially, 249 employees have met the inclusion criteria where they received the survey. Only 238 surveys were returned back to the researcher and 29 of which were excluded. The final number of surveys was 209. Main Results: • The study sample members were satisfied to some extent on working wages. • The study sample members were satisfied with their relationship with coworkers. • Members of the study sample were very satisfied with one dimension of worker co-workers, which is "my relationship with my colleagues at work." • Members of the study sample were satisfied with the leadership exercised by their supervisors at work. • Members of the study sample were very satisfied with one dimension of leadership exercised by the supervisors at work, which is "respect me by my superiors at work." • Members of the study sample were satisfied to some extent on the factor for promotion in employment. • Members of the study sample were satisfied with one dimension of the promotion at work, which is "My feeling towards my promotion in my work." • Members of the study sample were satisfied to some extent on the worker-job training. • The study sample members were satisfied with the social status achieved by their work. • The most significant factors affecting the career of job satisfaction among staff at the Presidency of the National Guard were a factor of satisfaction with my work colleagues at an average total (4.11 out of 5) followed by a factor of satisfaction with management way to work with an average (3.60 out of 5) followed by a factor of satisfaction with social status, which Fulfill work for them by an average (3.48 out of 5). • The least factors that affect the job satisfaction of employees at the Presidency of the National Guard were a factor of satisfaction with the training that is received with an arithmetic average of (3.08 out of 5) followed by a factor of the salary satisfaction with an average of (3.12 out of 5) followed by a factor of the promotion satisfaction with an average of (3.14 out of 5). • There was no significant influence of the independent variables (personal variables) on the dependent variable (job satisfaction) except the marital status variable. Conclusion :The researcher concluded with a number of recommendations including: work on all area to improve the level of job satisfaction among workers under the Presidency of the National Guard, determine the problems that limit the level of job satisfaction, and the development of appropriate ways to address them as recommended to work on create the appropriate working environment for employees, thus contributing to improving the level of job satisfaction.